2016
DOI: 10.3389/fncel.2016.00255
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen Protects Primary Rat Retinal Ganglion Cells from Chemical Hypoxia-Induced Apoptosis Through the Akt and PERK Pathways

Abstract: Retinal ganglion cells (RGCs) consume large quantities of energy to convert light information into a neuronal signal, which makes them highly susceptible to hypoxic injury. This study aimed to investigate the potential protection by baclofen, a GABAB receptor agonist of RGCs against hypoxia-induced apoptosis. Cobalt chloride (CoCl2) was applied to mimic hypoxia. Primary rat RGCs were subjected to CoCl2 with or without baclofen treatment, and RNA interference techniques were used to knock down the GABAB2 gene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 69 publications
5
17
0
Order By: Relevance
“…Present results indicate that the activation of GABAB receptors by GABA/baclofen can inhibit caspase activation after SCI in identifiable descending neurons, which is a key step to preventing the development of apoptosis and promoting neuronal survival. Previous work in other models of CNS injury also showed that a baclofen treatment can inhibit caspase activation (model of kainic-acid induced seizure in rats: Wei et al, 2012; models of ischemic brain injury in rats: Han et al, 2008;Liu et al, 2015; model of chemical hypoxia in retinal ganglion cells in rats: Fu et al, 2016). Our study shows that the activation of GABAB receptors can also prevent apoptosis after a traumatic SCI.…”
Section: Discussionsupporting
confidence: 75%
“…Present results indicate that the activation of GABAB receptors by GABA/baclofen can inhibit caspase activation after SCI in identifiable descending neurons, which is a key step to preventing the development of apoptosis and promoting neuronal survival. Previous work in other models of CNS injury also showed that a baclofen treatment can inhibit caspase activation (model of kainic-acid induced seizure in rats: Wei et al, 2012; models of ischemic brain injury in rats: Han et al, 2008;Liu et al, 2015; model of chemical hypoxia in retinal ganglion cells in rats: Fu et al, 2016). Our study shows that the activation of GABAB receptors can also prevent apoptosis after a traumatic SCI.…”
Section: Discussionsupporting
confidence: 75%
“…Using this system, we demonstrated that CoCl 2 was able to induce VSC4.1 motor neuronal ER stress and cause apoptosis in a dose-dependent manner. Our results are consistent with previous reports that the PERKeIF2α-ATF4 pathway was activated by CoCl 2 [44]. Then, we explored the effect of β-elemene on neuronal apoptosis induced by ER stress, with our results suggesting that β-elemene reduces VSC4.1 motor neuronal apoptosis by inhibiting the phosphorylation of PERK and eIF2α and the expression of ATF4.…”
Section: Discussionsupporting
confidence: 82%
“…Present results indicate that the activation of GABAB receptors by GABA/baclofen can inhibit caspase activation after SCI in identifiable descending neurons, which is a key step to preventing the development of apoptosis and promoting neuronal survival. Previous work in other models of CNS injury also showed that a baclofen treatment can inhibit caspase activation (model of kainic-acid-induced seizure in rats: 29 ; models of ischaemic brain injury in rats: 27 , 31 ; model of chemical hypoxia in retinal ganglion cells in rats: 66 ). Our study shows that the activation of GABAB receptors can also prevent apoptosis after a traumatic SCI.…”
Section: Discussionmentioning
confidence: 93%